Human B cell defects in perspective - Cunningham-Rundles, Charlotte (2012)
While primary immune defects are generally considered to lead to severe and easily recognized disease in infants and children, a number of genetic defects impairing B cell function may not be clinically apparent or diagnosed until adult life. The commonest of these is common variable immune deficiency, the genetic origins of which are beginning to be at least partially understood. CVID affects ≈ 1/25,000 Caucasians and is characterized by a marked reduction in serum IgG, almost always in serum IgA, and reduced serum IgM in about half of all cases; these defects continue to provide an opportunity to investigate the genes necessary for B cell function in humans. Recently, a small number of genes necessary for normal B cell function have been identified in consanguineous families leading to varying degrees of hypogammaglobulinemia and loss of antibody production. In other studies, whole-exome sequencing and copy number variation, applied to large cohorts, have extended research into understanding both the genetic basis of this syndrome and the clinical phenotypes of CVID.